Exploring association between food insecurity and depression among older adults in India - Ratna Patel; Shubham Kumar; Shekhar Chauhan (Elsevier, 2022)
Background: Depression is a significant health concern that is yet to be recognised as an important public health challenge in India. Furthermore, given the critical condition of food insecurity among older people in India, it is likely that they are more vulnerable to depression. The interplay of depression among older people resulting from food insecurity is an under-explored phenomenon in the Indian context. Therefore, this study examines the association between food insecurity and depression among older people in India. Methods: The study used data from the Longitudinal Ageing Study in India (LASI). Food insecurity was measured with a set of questions formed into dichotomous variable and depression was measured with Center for Epidemiological Studies Depression (CES-D scale). Binary logistic regression was performed to confirm the findings. Results: Results showed that older adults who reported food insecurity were more likely to be depressed (OR= 1.20; C.I.=1.03-1.25) than their younger counterparts. Furthermore, older adults who were independent for Activity of Daily Living (ADL) were less likely (OR= 0.73; C.I.=0.53-1.00) to report depression, whereas, female (OR= 1.12; C.I.=1.00-1.26) and never married (OR= 2.11; C.I.=1.18-3.79) older adults were more likely to be depressed than their respective counterparts. Conclusion: It is important to integrate mental health with food insecurity. Future studies may consider including mental health services with food assistance programs or vice versa.